Analysis of Students' Difficulties in Solving Numeracy Problems Based on PÃ³lyaâ€™s Theory - Egi Agustian1, (International Conference on Elementary Education, 2025)
This study uses a qualitative descriptive method to describe the difficulties faced by fifth-grade elementary school students in solving numeracy problems. The focus of this research is on numeracy content, covering basic mathematical operations and word problems, analysed based on specific indicators of students' numeracy skills. Data collection techniques involved administering numeracy problem tests and conducting in-depth interviews with several students as research samples. The results indicate that most students experience difficulties in understanding and solving word problems, especially in determining the appropriate solution steps. Students with high proficiency levels demonstrate good comprehension of the problems and are able to plan and execute solution steps adequately. Meanwhile, students with low proficiency levels generally struggle with planning solution steps, performing calculations accurately, and reflecting on the final results obtained. The conclusion of this study highlights the need for more interactive teaching strategies, the use of visual aids, and varied problem-solving exercises to help students overcome difficulties in understanding and solving numeracy problems.